The Effect of Religiosity on Work Ethic on Educators - Yanuar Putri Agustina; Ugung Dwi Ario Wibowo (UM Purwokerto Press, 2021)
This study aimed to determine the effect of religiosity on the work ethic of the educator at the State Police School (SPN) of the Central Java Police. This research is a quantitative study with 57 educators at the State Police School (SPN) of the Central Java Police. The data collection method used in this study is to use a work ethic scale with a reliability of 0.955, a religiosity scale with a reliability of 0.906. The data analysis technique used in this study was a simple linear regression analysis technique to determine the effect of religiosity on the work ethic of the State Police School (SPN) educators of the Central Java Police. The results showed that the calculated F = 0.942 and significant value = 0.000 (p <0.05), it can be concluded that the hypothesis is accepted, there is an influence of religiosity on the work ethic of the State Police School (SPN) educators of the Central Java Police. It is also known that the coefficient of determination is 0.369, which indicates that the influence of the independent variable (religiosity) on the dependent variable (work ethic) provides an effective contribution of 36.9%.